Evaluation of residual plastic strain distribution in dissimilar metal weld by hardness mapping. (1st October 2013) - Qiao, D; Zhang, W; Pan, T-Y; Crooker, P; David, S; Feng, Z
Abstract : The knowledge of residual plastic strains is a prerequisite for studying the stress corrosion cracking in dissimilar metal welds common to nuclear power plant structures. In this work, the distribution of residual equivalent plastic strains in a multipass dissimilar metal weld composed of nickel alloy 82 and austenitic stainless steel 304L is evaluated quantitatively through microhardness mapping. The contribution to hardness from the plastic strain (workhardening) is separated from that from the chemistry variation in the dissimilar metal weld. It is found that high equivalent plastic strains are predominately accumulated in the buttering layer, the root pass and the heat affected zone, which experience multiple welding thermal cycles. The final cap passes, experiencing only one or two welding thermal cycles, exhibit less plastic strain accumulation. Moreover, the experimental residual plastic strains are compared with those predicted using an existing weld thermomechanical model with two different strain hardening rules. The importance of considering the dynamic strain hardening recovery due to high temperature exposure in welding is discussed for the accurate simulation of weld residual stresses and plastic strains. Finally, the experimental result reveals that the typical post-buttering heat treatment for residual stress relief may not completely eliminate the residual plastic strains in the buttering layer.